Mouse Bone Marrow-Derived Endothelial Progenitor Cells Do Not Restore Radiation-Induced Microvascular Damage. - Seemann, Ingar; te Poele, Johannes A. M.; Hoving, Saske; Stewart, Fiona A. (ISRN Cardiology, 2014)
Background. Radiotherapy is commonly used to treat breast and thoracic cancers but it also causes delayed microvascular damage and increases the risk of cardiac mortality. Endothelial cell proliferation and revascularization are crucial to restore microvasculature damage and maintain function of the irradiated heart. We have therefore examined the potential of bone marrow-derived endothelial progenitor cells (BM-derived EPCs) for restoration of radiation-induced microvascular damage. Material & Methods. 16 Gy was delivered to the heart of adult C57BL/6 mice. Mice were injected with BM-derived EPCs, obtained from Eng+/+ or Eng+/- mice, 16 weeks and 28 weeks after irradiation. Morphological damage was evaluated at 40 weeks in transplanted mice, relative to radiation only and age-matched controls. Results. Cardiac irradiation decreased microvascular density and increased endothelial damage in surviving capillaries (decrease alkaline phosphatase expression and increased von Willebrand factor). Microvascular damage was not diminished by treatment with BM-derived EPCs. However, BM-derived EPCs from both Eng+/+ and Eng+/- mice diminished radiation-induced collagen deposition. Conclusion. Treatment with BM-derived EPCs did not restore radiation-induced microvascular damage but it did inhibit fibrosis. Endoglin deficiency did not impair this process.